Investigation into the presence and functional significance of proinsulin C-peptide in the female germline†. Issue 5 (30th January 2019) - Martin, Jacinta H; Aitken, R John; Bromfield, Elizabeth G; Cafe, Shenae L; Sutherland, Jessie M; Frost, Emily R; Nixon, Brett; Lord, Tessa
Abstract: Diabetes is associated with poor oocyte quality and the dysregulation of ovarian function and is thus a leading contributor to the increasing prevalence of female reproductive pathologies. Accordingly, it is well-established that insulin fulfills a key role in the regulation of several facets of female reproduction. What remains less certain is whether proinsulin C-peptide, which has recently been implicated in cellular signaling cascades, holds a functional role in the female germline. In the present study, we examined the expression of insulin, C-peptide, and its purported receptor; GPR146, within the mouse ovary and oocyte. Our data establish the presence of abundant C-peptide within follicular fluid and raise the prospect that this bioactive peptide is internalized by oocytes in a G-protein coupled receptor-dependent manner. Further, our data reveal that internalized C-peptide undergoes pronounced subcellular relocalization from the ooplasm to the pronuclei postfertilization. The application of immunoprecipitation analysis and mass spectrometry identified breast cancer type 2 susceptibility protein (BRCA2), the meiotic resumption/DNA repair protein, as a primary binding partner for C-peptide within the oocyte. Collectively, these findings establish a novel accumulation profile for C-peptide in the female germline and provide the first evidence for an interaction between C-peptide and BRCA2. This interaction is particularly intriguing when considering the propensity for oocytes from diabetic women to experience aberrant meiotic resumption and perturbation of traditional DNA repair processes. This therefore provides a clear imperative for further investigation of the implications of dysregulated C-peptide production in these individuals. Abstract : Proinsulin C-peptide is internalized by the mouse oocyte and thereafter may play a key role in folliculogenesis and embryogenesis.